Epizootic ulcerative fish disease syndrome - Kar, Devashish; ScienceDirect eBooks (London, UK : Academic Press, 2015)
Epizootic Ulcerative Fish Disease Syndrome covers both the background and current information on the EUS disease relevant to fisheries and aquaculture delivered in a systematic and succinct way. The book is an essential resource for the aquaculture and fisheries researcher interested in finding solutions to the spread of the disease across the globe and students in relevant programs, including an in-depth description and analysis of the disease, as well as the structure and composition of the virus, while offering prevention and control methodologies. Clinical veterinarians, aquacultur.
""6.5 climate vis-a-vis seasonality""""6.6 environmental parameters of significance to fish health""; ""6.7 works by the author of the present treatise""; ""6.8 similar works done on epizootic ulcerative syndrome by other workers""; ""6.9 related works on epizootic ulcerative syndrome done by other workers""; ""6.10 works done by different workers in different places""; ""6.11 works done on different parameters related to epizootic ulcerative syndrome""; ""6.12 works done on eus in relation to socioeconomics""; ""6.13 taxonomic analysis""; ""6.14 etiological agents of eus""
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed August 20, 2015).
Elsevier
Keywords: Fishes -- Infections; Fishes -- Diseases -- Molecular aspects; TECHNOLOGY & ENGINEERING / Agriculture / General; Fishes -- Diseases -- Molecular aspects; Fishes -- Infections; Electronic books